(untitled) (Journal of Innovation in Academia, 2025)
This paper aims to assess the extent of perceived empowerment and job involvement among part-time faculty members. It also examines the relationship between empowerment and job involvement among part-time faculty members and explores how socio-demographic characteristics influence the relationship between empowerment and job involvement among part-time faculty members. A scientifically prepared questionnaire is used to collect the primary data by considering various demographic characteristics, job involvement, and empowerment of part-time faculty on 10 constituent campuses. These campuses are selected judgmentally and conveniently. The results show a very strong positive association between job involvement and empowerment. This suggests that as part-time faculty members feel more empowered, their level of job involvement also increases significantly. High empowerment, which includes having a sense of meaning and competence, self-determination, and impact, is strongly associated with high job involvement. Only marital status and education are the two most important socio- demographic characteristics.